Knives in Third Space - Mukkada, Roy J.; Mathew, Pradeep G. (Journal of Digestive Endoscopy, 2022)
Endoscopic mucosal resection (EMR) has always been done with a snare. The maximum diameter of the snare is usually 2 cm and the largest lesion that can be removed in one piece is usually maximum of 2 cm. In EMR, after the elevation of the submucosa, snares are used for the resection of the mucosal lesion; however, for endoscopic submucosal dissection (ESD), special knives are required, which have various uses in different areas of the gastrointestinal tract. ESD knives have developed and evolved over the past 30 years allowing it to be performed safely. It allows very precise cutting of the mucosa as well as dissection of the submucosal tissue planes. This review discusses some of the more commonly used knives.
Keywords: dual knife; endoscopy knives; ESD; IT knife; TT knife